2017
DOI: 10.1590/0103-6440201701476
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Loss in Patients under Periodontal Maintenance in a Private Practice: A Retrospective Study

Abstract: The aim of the present study was to evaluate the incidence and causes of tooth loss in periodontal subjects from a private practice in Brazil. Two trained examiners extracted data from the records of subjects who sought periodontal treatment from 1980 to 2013. Only records of patients who completed the non-surgical periodontal treatment and had at least one visit for maintenance were included. Data were analyzed by chi-square test, Student's t-test, Kaplan-Meier survival curve and Cox regression. A total of 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
(29 reference statements)
0
18
1
2
Order By: Relevance
“…To clarify the meaning of tooth loss in the epidemiologic context, it would be helpful to use longitudinal data. A few studies report on tooth survival over time or trends in repeated cross‐sectional samples but most rely on self‐reported tooth loss with limitations in validity, or are performed in selected patient groups with limitations in generalizability into the general population . To date, the largest published longitudinal analysis of changes in dental status comes from the Dunedin study, a prospective cohort study of approximately 1000 participants born in 1972/1973 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To clarify the meaning of tooth loss in the epidemiologic context, it would be helpful to use longitudinal data. A few studies report on tooth survival over time or trends in repeated cross‐sectional samples but most rely on self‐reported tooth loss with limitations in validity, or are performed in selected patient groups with limitations in generalizability into the general population . To date, the largest published longitudinal analysis of changes in dental status comes from the Dunedin study, a prospective cohort study of approximately 1000 participants born in 1972/1973 .…”
Section: Introductionmentioning
confidence: 99%
“…A few studies report on tooth survival over time or trends in repeated cross-sectional samples [14][15][16][17][18][19] but most rely on self-reported tooth loss with limitations in validity, 14,16,17 or are performed in selected patient groups with limitations in generalizability into the general population. 19,20 To date, the largest published longitudinal analysis of changes in dental status comes from the Dunedin study, a prospective cohort study of approximately 1000 participants born in 1972/1973. [21][22][23] This study provides insight up to age 38, where levels of tooth loss remain low.…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to those from a study in a general dental clinic by Axelsson et al 7 In another study showing that the primary cause of TL was periodontal disease, data samples were obtained from three periodontists' private offices. 30 In another study, patient data were obtained after treatment by a periodontist. 31 In these studies, most patients were considered to be at high risk of periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that the most frequent cause of TL, even with maintenance therapy, was periodontal disease. 30,31 Various factors, such as age, smoking, diabetes mellitus (DM), and others, are also related to TL, and the risk of TL increases with the presence of additional non-vital teeth (those that have undergone root canal treatment). 30,[32][33][34] Despite reports that various factors affect TL, many of these studies were conducted under special circumstances, such as at a university hospital or within a specialist clinic, where patient demographics were limited.…”
Section: Introductionmentioning
confidence: 99%
“…A assistência odontológica em longo prazo é um procedimento baseado em visitas regulares estabelecidas após o tratamento periodontal ativo, bem conhecido como uma estratégia essencial para preservar a saúde periodontal para pacientes tratados e reabilitados e como estratégia preventiva para a perda dentária. A doença periodontal foi a causa de 38% das perdas dentárias, e os pacientes com assistência odontológica regulares perderam menos dentes(Stadler et al, 2017, Suzuki et al, 2017. A razão número um para não visitar um dentista mais frequentemente é o custo, seguido de medo do dentista, localização e tempo inconveniente(Deguchi et al, 2017).…”
unclassified